PEMBERDAYAAN USAHA KECIL DAN MENENGAH (UKM) PRODUK PANGAN TRADISIONAL DENGAN TEKNOLOGI DIGITAL DI KELURAHAN SARIO KOTABARU, KOTA MANADO - Tooy, Dedie; Longdong, Ireine Adriana; Pinatik, Herry Frits; Lengkey, Lady E.Ch.; Koapaha, T.; Mamuaja, Christine; Laleleh, Sherina; Walangitan, Khesilya E.; Mona, Frits (LPPM Universitas Bina Bangsa, 2024)
Small and medium-sized enterprises (SMEs) in traditional food processing often face challenges such as limited marketing channels that rely mostly on word-of-mouth with restricted reach, unstructured financial management, and monotonous business activities. This Community Partnership Program (PKM) was conducted in Sario Kotabaru Village, Sario District, Manado City, targeting two SMEs that produce and sell traditional North Sulawesi foods, specifically